Real-time imaging theory, techniques, and applications - Laplante, Phillip A.; Stoyenko, Alexander D. (IEEE Press, 1996)
Summary : "Ground-breaking anthology provides authoritative guidance on tackling the core real-time processing performance trade-offs involved in image resolution, storage and input/output bandwidth, and synchronization. DLC: Image processing Digital techniques."